Influence of workplace incivility on counterproductive work behavior: Mediating role of emotional exhaustion, organizational cynicism and the moderating role of psychological capital - Sadia Butt; Naveed Yazdani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Drawing on conservation of resources (COR) theory, this study investigates association of workplace incivility (WI) with counterproductive work behavior (CPWB) of banking employees in Pakistan. In addition, mediating role of emotional exhaustion (EE), organizational cynicism (OCY) and moderating role of psychological capital (Psy-Cap) were also examined. A structured questionnaire was used to obtain data from 215 banking employees of Lahore, Pakistan after applying stratified random sampling. Data was analyzed applying mediation / moderation regression using Hayes Process Macro in SPSS 21. Findings reveal that workplace incivility has significant and positive association with CPWB. While, emotional exhaustion and cynicism partially mediate positive association between WI and CPWB. Moreover, psychological capital in interaction with WI has significant moderating impact and weakens the positive association between WI and CPWB. Study findings are useful for practitioners because our results reveal moderating role of Psy-Cap as coping mechanism on association of WI and CPWB. Management can benefit from the buffering effect of Psy-Cap to help and train employees dealing with uncivil conducts and reduce CPWBs at workplace.
Keywords: 330; workplace incivility; counterproductive work behavior; emotional exhaustion; organizational cynicism; psychological capital; banking sector; Pakistan